Public Perceptions on the Importance of Ecosystem Services From Vulnerable Forest: A Case Study of Ampang Forest Reserve, Selangor, Malaysia - Gai, Mei Yin; Hassan, Muhammad Luqman; Anak Empidi, Arlixcya Vinnisa; Juraimi, Umi Farishaanum; Mohd Noorazman, Nurashikin; Emang, Diana (Institut Pertanian Bogor (IPB University), 2024)
Forest reserve gazettement affects the sustainability of forests by altering their ecological function and threatening human livelihood. This study examines a recently degazetted forest, using a survey among 120 local respondents living near Ampang Forest Reserve (AFR) in Selangor, Malaysia. The simple random sampling technique was implemented to reduce sampling bias, and descriptive and correlation statistics were used in the analysis. The study aims (i) to examine the public perceived importance of forest ecosystem services from AFR, (ii) to determine public awareness of a range of environmental threat levels towards AFR’s ecosystem services, and (iii) to assess public agreement on conservation measures that could increase protection and ensure the sustainability of ecosystem services from the remaining area of AFR. The result revealed all ecosystem services were perceived as important, and the public was mostly aware of the environmental threats. At the same time, conservation measures should be implemented to protect and ensure the sustainability of ecosystem services from AFR. This study provides insight into public perceptions of the importance of forest ecosystem services derived from vulnerable forest reserves. It indicates the relevance and need for better protection in high-risk forest areas as local livelihood depends on its significant ecological roles.